Lifestyle Intervention for Weight Loss and Cardiometabolic Changes in the Setting of Glucokinase Regulatory Protein Inhibition: Glucokinase Regulatory Protein-Leu446Pro Variant in Look AHEAD. (February 2016) - Belalcazar, L. Maria; Papandonatos, George D.; Erar, Bahar; Peter, Inga; Alkofide, Hadeel; Balasubramanyam, Ashok; Brautbar, Ariel; Kahn, Steven E.; Knowler, William C.; Ballantyne, Christie M.; McCaffery, Jeanne M.; Huggins, Gordon S.
Abstract : Background—: Glucokinase regulatory protein (GCKR) inhibitors offer a novel treatment approach for glucose control in diabetes mellitus; however, their cardiometabolic effects, particularly in relation to increased triglycerides and C-reactive protein (CRP) levels, are of concern. GCKR Leu446Pro is a common variant associated with reduced GCKR function, increased triglycerides, and CRP. Methods and Results—: We investigated whether a 1-year intensive lifestyle intervention (ILI) for weight loss would avert the unfavorable cardiometabolic effects associated with GCKR Leu446Pro when compared with a diabetes mellitus support and education arm in overweight/obese individuals with type 2 diabetes mellitus with triglyceride (n=3214) and CRP (n=1411) data participating in a randomized lifestyle intervention study for weight loss, Action for Health in Diabetes Mellitus (Look AHEAD). Once demographics, medication use and baseline adiposity, and fitness were accounted for, ILI did not modify the baseline association of GCKR-Leu446Pro with elevated triglycerides (β±SE=0.067±0.013, P =1.5×10 −7 and β±SE=0.052±0.015, P =5×10 −4 ) or with elevated CRP (β±SE=0.136±0.034, P =5.1×10 −5 and β±SE=0.903±0.038, P =0.015) in the overall sample and Non-Hispanic Whites, respectively. The lack of a protective effect from ILI at 1 year when compared with diabetes mellitus support and education (ILI versus diabetes mellitus support and education interaction for triglyceride and CRP change, respectively: P =0.64 and 0.37 in the overall sample; P =0.27 and 0.05 in Non-Hispanic Whites) persisted after additional adjustment for changes in adiposity and fitness. Conclusions—: Moderate improvements in adiposity and fitness with ILI did not mitigate the adverse cardiometabolic effects of GCKR inhibition in overweight/obese individuals with diabetes mellitus. Abstract : Supplemental Digital Content is available in the text.